2010
DOI: 10.1007/s11581-010-0462-x
|View full text |Cite
|
Sign up to set email alerts
|

A perturbed hard-sphere equation of state extended to imidazolium-based ionic liquids

Abstract: A perturbed hard-sphere equation of state (EOS) has been previously employed to predict pressure-volumetemperature properties of some ionic liquids (ILs) with phosphonium-, pyridinium-, and pyrrolidinium cations. In this work, we have extended the considered EOS to another class of ILs in compressed states. This class consists of 14 imidazolium-based ILs. The predicted densities were compared with those obtained from the experiment, over a broad pressure range from 0.1 to 200 MPa. From 1,122 data points examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…The overall AAD of the predicted surface tension for 81 data points using the present model, Alavianmehr et al, QSPR, and CS-GC methods were found to be 0.29, 1.45, Table 7 The scaling constants to be used in Eq. (25)and AAD (%) of the calculated surface tension using the present model and those obtained by Alavianmehr et 7.73, and 4.14%, respectively. As we can see from Table 7, the present model is the most accurate among other abovementioned methods.…”
Section: Extension To Mixturessupporting
confidence: 63%
See 1 more Smart Citation
“…The overall AAD of the predicted surface tension for 81 data points using the present model, Alavianmehr et al, QSPR, and CS-GC methods were found to be 0.29, 1.45, Table 7 The scaling constants to be used in Eq. (25)and AAD (%) of the calculated surface tension using the present model and those obtained by Alavianmehr et 7.73, and 4.14%, respectively. As we can see from Table 7, the present model is the most accurate among other abovementioned methods.…”
Section: Extension To Mixturessupporting
confidence: 63%
“…Aparicio et al [5] reviewed the available predictive models as well as experimental data reported in literature for the thermophysical properties and especially density and PVT behavior of ionic liquids. Further, a perturbed hard-sphere equation of state has been employed to predict the pressure-volume-temperature properties of some pure and mixture of ionic liquids [6][7][8][9]. Also, they predicted the volumetric properties of ILs using Ihm-Song-Mason (ISM) [10] and Tao-Mason [11] equations of state.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works by Hosseini et al [1][2][3] led to the development of a perturbed hard-sphere EOS for predicting the pressurevolume-temperature (PVT) properties of several classes of pure ionic liquids. Our objective in this work was to present a more reliable equation of state than previous works.…”
Section: Introductionmentioning
confidence: 99%
“…(1) They are the favorite electrolytes in lithium rechargeable batteries [4] and supercapacitors [5]; (2) theses materials can also be used as thermal fluids for heat storage by combining their high heat capacity, thermal stability, and negligible vapor pressure [6]; and (3) their interesting solvent properties make them well known as green solvents for the future [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation